2005
DOI: 10.1002/mds.20629
|View full text |Cite
|
Sign up to set email alerts
|

Effect of levodopa on pain threshold in Parkinson's disease: A clinical and positron emission tomography study

Abstract: Patients suffering from Parkinson's disease (PD) frequently experienced painful sensations that could be in part due to central modification of nociception. We compared pain threshold before and after administration of levodopa in PD patients and in controls, and investigated cerebral activity with positron emission tomography (PET) during experimental nociceptive stimulation. Pain threshold was determined using thermal stimulation during two randomized conditions: off and on. We performed H(2) (15)O PET analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
235
4
15

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(274 citation statements)
references
References 28 publications
20
235
4
15
Order By: Relevance
“…Fifth, patients were receiving medications during the trial. Dopamine might modulate sensory thresholds in patients with PD by an antinociceptive effect or pain modulation (Brefel-Courbon et al, 2005;Gerdelat-Mas et al, 2007;Cury et al, 2016). At the same time, examining all patients while on medication made it possible to isolate the effect of cannabis on pain threshold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, patients were receiving medications during the trial. Dopamine might modulate sensory thresholds in patients with PD by an antinociceptive effect or pain modulation (Brefel-Courbon et al, 2005;Gerdelat-Mas et al, 2007;Cury et al, 2016). At the same time, examining all patients while on medication made it possible to isolate the effect of cannabis on pain threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Some noted no differences in heat pain intensity between 'on' and 'off' states in patients with motor fluctuations, suggesting that the QST results were not affected by dopamine (Djaldetti et al, 2004;Nandhagopal et al, 2010). Others, however, found that dopaminergic medications increased the heat pain threshold in patients with PD and primary central pain (Schestatsky et al, 2007) and that levodopa lessened nociceptive pain and normalized the pain response in the 'on' state (Brefel-Courbon et al, 2005;Gerdelat-Mas et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, in 40.7% of these patients this was not observed, suggesting that in addition to the patients who were in "wearing-off" status, there must have been nondopaminergic mechanisms related to primary pain in PD 14 . Recent studies had shown a reduction of the threshold to pain in PD 14,28 . Brefel-Courbon et al 28 investigated the pain in PD patients and controls by means of thermal stimulation and cerebral activity with positron emission tomography.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies had shown a reduction of the threshold to pain in PD 14,28 . Brefel-Courbon et al 28 investigated the pain in PD patients and controls by means of thermal stimulation and cerebral activity with positron emission tomography. They concluded that pain threshold in PD patients in off condition was significantly lower than in controls and the administration of levodopa significantly raised pain threshold in PD patients, but not in controls.…”
Section: Methodsmentioning
confidence: 99%
“…O, Brefel-Courbon et al [11] have observed that PD patients off medication have a reduced pain threshold and that this was associated with a greater activation of the pain matrix (insula, cingulate and prefrontal cortex). Levodopa reduces this abnormal cortical recruitment and increases pain threshold [12].…”
mentioning
confidence: 97%